Calving Out a Space to Exist: “Marked” Identities in Polar Science’s “Unmarked Spaces” - Anya Lawrence; Luis Escobedo (Earth Science, Systems and Society)
For minority employees at the British Antarctic Survey (BAS), the organisation has enriched their careers, while offering equality, diversity and inclusivity (EDI) measures to mitigate some of the issues affecting them. However, the way they belong to BAS remains impacted by the structural and everyday practices that shape their lives through identity processes. In light of BAS’ ambition to enhance Antarctic science opportunities to underrepresented groups, this study engages with the lived experiences and perspectives of minority BAS employees at their workplace. We argue that while they experience and perceive rejection, discrimination and exclusion, these practices are tangled up in the dominant and majority group’s internal identification processes rather than by the isolated and deliberate action of its members. Those who are part of the “unmarked” dominant group have, from an early age, internalised national, ethnic, gender, and other forms of belonging and continue to engage in new boundary demarcation in the present. In this way, it is in their contact with non-members, that the boundaries between the “marked” and “unmarked” come to the fore, even when the intention of the dominant group may be to erode such boundaries.